Oceanographic Data of the 45th Japanese Antarctic Research Expedition from December 2003 to March 2004 - オガタ, ジュン; ナバエ, ヤスシ; Ogata, Jun; Nabae, Yasushi (National Institute of Polar Research, 2006)
P(論文) departmental bulletin paper